RESPON PERTUMBUHAN TANAMAN JARAK PAGAR (Jatropha curcas Linn.) YANG DIBERI PUPUK KANDANG KOTORAN SAPI DAN PUPUK NPK MUTIARA PADA TANAH BERPASIR (Growth Of Plant Jatropha (Jatropha curcas Linn.) Fertilized With Cow Manure and NPK Mutiara On Sandy Soil) - Widyawati W. (AgriPeat, 2016)
This study aim to determine the growth of Jatropha curcas by applying of cow manure and NPK mutiara fertilizer on sandy soil. The design used in this study was Factorial Group Randomized Design with two factors. The first level was cow manure consist of 4 namely, without giving 0, 1, 2, 3 t.ha-1 of per crop. The second level was the giving of mutiara fertilizer namely, without giving 0, 100, 150, 200 kg.ha-1. The results showed that there was significant interaction between cow manure and NPK mutiara fertilizer on plant height and leaves number of Jatropha curcas on sandy soil. The dosage of 3 t.ha-1 of cow manure and 200 kg.ha-1, NPK mutiara fertilizer were able to increased the plant height and number of leaves, meanwhile the each of single factor had a significant interaction on the plant height, leaves number, diameter of stem and number of branches. The K3N3 was the best treatment on overall the variable observed